Cerita Minggu Pagi: Model Penguatan Literasi Anak melalui Membaca Nyaring (Reading Aloud) Berbasis Komunitas Towaine Mandar - Rostina Rostina; A. Reski Almaida Dg Macenning; Zuhriah Zuhriah; Miftahul Jannah; Nur Rahmah; Amiqah Amiqah (Jurnal Pelayanan Masyarakat, 2026)
This community service program aimed to strengthen children's literacy skills through a community-based reading aloud model implemented in the “Cerita Minggu Pagi” program. The activity was motivated by the low level of children's reading interest and limited literacy stimulation in both family and community environments. A participatory community-based approach was applied by involving Towaine Mandar as local community, volunteers, and parents in creating a supportive literacy ecosystem. The program was conducted in Desa Baru, Luyo District, Polewali Mandar Regency, with 20–30 children aged 5–12 years participating in each session. The implementation consisted of preparation, execution, and evaluation stages. The main activity involved interactive reading aloud supported by storytelling, discussions, and follow-up activities such as retelling, drawing, and role-playing. Data were collected through participatory observation, informal interviews, and documentation, and were analyzed using a descriptive qualitative approach. The results showed that the program had a positive impact on children's literacy development, including improvements in story comprehension, vocabulary acquisition, speaking skills, and self-confidence. In addition, children demonstrated increased reading interest and active participation during the activities. The use of reading aloud techniques—such as articulation, intonation, pauses, and expression—created an engaging and meaningful learning experience. Furthermore, community involvement contributed significantly to the sustainability of the program.